POST TRAUMATIC STRESS DISORDER IN THOMAS HARRIS’ HANIBAL RAISING - Sry Mai Linda Gea (STBA Prayoga Padang, 2018)
This research aims to analyze the Hannibal Lecter‟s PTSD in Thomas Harris‟ Hannibal Rising novel. It describes that the main character has psychological problem. He suffers from Post Traumatic Stress Disorder. There are two questions that appear to discuss i.e. the causes and the symptoms of Post Traumatic Stress Disorder perceived by Hannibal Lecter the main character. This research uses theory of Post Traumatic Stress Disorder by Glenn R. Schiraldi. There are some concepts of the theory i.e. symptoms and causes of Post Traumatic Stress Disorder. This concept helps this research to describe the causes and the symptoms of Post Traumatic Stress Disorder that are perceived by Hannibal Lecter in the novel. The result of this research shows that war situation is one of thecauses of Post Traumatic Stress Disorder.Hannibal Lecter‟s life changed after he experienced war situation such as witnessing the death of parent and witnessing the murder of siter Mischa in the war.Then, he also showsthe symptoms of Post Traumatic Stress Disorder after experiencing the war. Those are flashback, troubled sleep, irritability of anger, trouble remembering, and feeling detached from others.